Implementasi Fungsi Pengarahan dan Pengendalian dalam Manajemen Pendidikan di SMP Panggudi Luhur Domenico Savio Semarang - Hermania Bhoki; Vinsensius Bawa Toron Bawa Toron (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
Quality education is an indicator of the success of educational institutions in implementing the role of education management appropriately. This article intends to describe and examine the application of the role of direction and control in educational management at the Panggudi Luhur Domenico Savio Junior High School Semarang. Data obtained through in-depth interviews with informants and documentation. Data analysis uses the method discovered by Miles and Huberman. The research concludes that Panggudi Luhur Junior High School Domenico Savio Semarang applies the function of directing and controlling function in education management well. The directing function is carried out by the principal by guiding, suggesting, giving encouragement, directions and instructions so that teachers and employees personally and communally can work hard, work fast, work productively as well as cooperate and work together well, correctly, according to their duties and functions. Internal and external control is carried out by conducting academic supervision to determine the quality and quantity of teacher work in carrying out its role in planning, implementing and evaluating learning based on quality standards set in the framework of achieving the school's vision, mission and goals.